Socioenvironmental Factors of Rheumatic Heart Disease among School-Going Children in Sarawak, Malaysia: A Mixed-Method Study - Rudy Ngau, Ajeng; Md Mizanur, Rahman; Asri, Said; Mohamed Ameenudeen, Sultan; Goh, Greta Miranda; Abg Safuan, Adenan; Muhammad Siddiq, Daud; Mohd Faiz, Gahamat (Horizon Research Publishing, 2023)
Socioenvironmental elements could explain the primordial and primary prevention of Rheumatic Heart Disease (RHD) in the local context. A well-planned, encompassing way to deal with RHD in the local setting is essential. Therefore, this study sought to investigate the socioenvironmental determinants of RHD among school-going children and to investigate the aetiology of RHD in the local setting. This study was conducted as a sequential explanatory mixed-methods design. A cross-sectional study was conducted in the first phase, followed by a qualitative study based on the grounded theory approach. The study was conducted in Kuching, Samarahan and Miri divisions in Sarawak among primary and secondary school-going children. The cross-sectional data collection was conducted via face-to-face interviews, while the qualitative phase was conducted via in-depth interviews. There was a preponderance of low socioeconomic status and large family size with RHD. Based on the grounded theory approach, the causes of rheumatic heart disease were classified into internal and external factors. After integrating the findings, the qualitative findings confirmed the quantitative results by confirmation and expansion without discordance. The findings would be vital for the management of RHD in terms of implementations in practice, theory, and subsequent research, as the factors were explained in the local context.